Estudio de prefactibilidad para la instalación de una planta productora de alimento BARF para mascotas - Jimenez Maldonado, Micaela Gloria (2023)
This paper will evaluate the feasibility of creating a plant for the production of BARF (Biologically Appropriate Raw Food) for dogs and cats. Chapter I presents the commercial, technological and economic-financial justifications. Likewise, the methodology to be used in the work will be proposed. Chapter II explores the needs of the clients through a market study, as well as the demand for the project by means of a survey of the target public; in addition, the marketing mix is proposed. Chapter III defines the macro and micro-location of the plant; in this section the factors to be considered are analyzed using the ranking of factors method. Then, in Chapter IV, the optimum plant size is calculated by evaluating five concepts: size-market, size-financing, size-technology and size-production resources, in order to determine the concept that will restrict production capacity. For Chapter V, the plant layout is proposed, considering the area necessary for production, which will be calculated using the Guerchet method. In addition, a detailed plan of the plant is designed. Chapter VI determines the type of organization and the tax regime, as well as the function of the employees directly and indirectly involved in production and the net salaries to be paid. Chapter VII calculates the necessary investment, production costs and operating budgets, and concludes with an evaluation of the economic and financial viability of the project. Chapter VIII the indicators that determine the social impact of the company will be calculated and interpreted. Finally, it is concluded that the proposed BARF food production plant is commercially, technically, economically, financially and socially viable.